2015
DOI: 10.1088/0004-637x/810/2/114
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Photoionization of Polycyclic Aromatic Hydrocarbon Molecules Carrying an Ethynyl Group

Abstract: The life cycle of the population of interstellar polycyclic aromatic hydrocarbon (PAH) molecules depends partly on the photostability of the individual species. We have studied the dissociative photoionization of two ethynylsubstituted PAH species, namely, 9-ethynylphenanthrene and 1-ethynylpyrene. Their adiabatic ionization energy and the appearance energy of fragment ions have been measured with the photoelectron photoion coincidence spectroscopy technique. The adiabatic ionization energy has been found at 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 79 publications
6
17
0
Order By: Relevance
“…Two minor peaks were found at m/z values 200 and 201 as demonstrated with Interestingly, only [1EtyPyr − H] + fragment ions were observed in our previous study (Rouillé et al 2015). The present detection of supplementary fragments is attributed to a longer residence time of the excited ions in the acceleration zone, which is a consequence to using acceleration fields of 80 and 160 V cm −1 instead of 355 V cm −1 .…”
Section: Fragment Ionssupporting
confidence: 77%
See 1 more Smart Citation
“…Two minor peaks were found at m/z values 200 and 201 as demonstrated with Interestingly, only [1EtyPyr − H] + fragment ions were observed in our previous study (Rouillé et al 2015). The present detection of supplementary fragments is attributed to a longer residence time of the excited ions in the acceleration zone, which is a consequence to using acceleration fields of 80 and 160 V cm −1 instead of 355 V cm −1 .…”
Section: Fragment Ionssupporting
confidence: 77%
“…The destruction of interstellar molecules proceeds mainly through photodissociation triggered by impinging VUV photons. For that reason, we have evaluated experimentally the photostability of two ethynylsubstituted PAH cations (Rouillé et al 2015). We have concluded that ethynyl-substituted PAH species are as photostable as the corresponding regular species, whereas it had been previously observed that methylated and hydrogenated PAH molecules are less photostable (Jochims et al 1999).…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, we also considered the 9-ethynylphenanthrene (orange dotted line), also likely to form in this zone. We used for this species the referenced spectrum previously determined by Rouillé et al 74 .…”
Section: Analysis Of the Species At M/z (C 16 H )mentioning
confidence: 99%
“…226 m/z is often attributed to CP-PAHs likely involved in the soot nucleation process 11,12,101 Among the other potential candidates, we also considered the 1-ethynyl-pyrene , the spectrum of which has been recorded by Rouillé et al 74 As for previous mass analyses, we report in fig. 10 As seen in fig.…”
Section: Analysis Of the Species At 226 M/z (C 18 H 10 )mentioning
confidence: 99%
See 1 more Smart Citation